COMPARISON OF STUDENT SATISFACTION BETWEEN ONLINE AND OFFLINE LEARNING USING SERVQUAL DATA ANALYSIS AND CARTESIAN DIAGRAMS IN FACULTY OF ISLAMIC ECONOMICS AND BUSINESS ISLAM IAIN PONTIANAK - Hani Meilita Purnama Subardi; tirofirman man firman (Fakultas Ekonomi dan Bisnis Islam, 2023)
This research was conducted to determine student satisfaction in online and offline learning for students of the Islamic Economics Study Program at the Pontianak Islamic Institute in 2022. The data used in this research is data on the number of students in semester 1 and semester 7 using Servqual data analysis and Cartesian diagrams. The Servqual test results from this research found that the performance of the Sharia Economics study program at FEBI IAIN Pontianak was above the expectations of students who carried out online teaching and learning. while the Cartesian Diagram shows that the distribution of 28 question attributes for students studying face-to-face shows that performance is in line with student expectations based on questions 2, 3, 4, 9, 15, 17, 23 and 26, while online learning is included in the category these are question items 4, 7, 8, 10, 21, 25 and 27. Lastly, the Customer Satisfaction Index (CSI) test results showed a result of 80.36%, meaning that students who studied face-to-face in semester 1 were satisfied with the service performance provided by the Sharia Economics Study Program FEBI IAIN Pontianak, while the online CSI result was 71, 94%, meaning that students who were online in semester 7 were quite satisfied with the service performance provided by the Sharia Economics Study Program FEBI IAIN Pontianak.